KEGIATAN JENAYAH DI KEDAH MENERUSI SURAT-MENYURAT SULTAN ABDUL HAMID (SMSAH) - Abd Aziz, Mohd Kasturi Nor bin (SEJARAH: Journal of the Department of History, 2017)
This article discusses social issues that occurred in Kedah through an examination of the collection of letters of Sultan Abdul Humid (SMSAH) which are related to robberies, theft, homicide, injury inflictineizt on individuals, female abductions and the involvement of high- ranking management officers in crime. These criminal activities had a negative influence on the socio-economic development and political stability in Kedah. These social issues had drawn the attention of Kedah’s goverment under the leadership of Sultan Abdul Humid with the aid of his local officials who later took several steps to reduce the crime rate by enforcing laws, cooperating with the British as well as the Siamese and the formation of a police force. Based on the collection of letters of Sultan Abdul Hamid and some Kedah Annual Report, this study shows that social issues were a serious concern in Kedah during the reign of Sultan Abdul Humid.